The First Compendium – on the 10th Anniversary of the Foundation of Tematy i Konteksty - Pasterska, Jolanta; Rokosz, Elżbieta; Stanisz, Marek (Tematy i Konteksty, 2021)
A Selection of the Decade is a special issue of Tematy i Konteksty, a literary studies journal which has been published in Poland since 2011. This special issue is a collection of articles that were published in Polish in former issues of the journal and have now been translated into English to reach English-speaking readers.